Impact of pycnogenol on acetaminophen-induced hepatorenal damage - (:unkn) unknown (AMG Transcend Association, 2022)
We investigated the protective effects of pycnogenol (PYC), a natural anti-oxidant with an anti-inflammatory effect, on the acetaminophen (APAP)-induced hepatorenal injury in rats. Wistar albino rats were divided into four experimental groups: control, PYC (10 mg/kg, ip), APAP (1000 mg/kg), and APAP+PYC groups. Rats were decapitated 24 hours after the APAP injection, and their blood was taken to determine blood urea nitrogen (BUN), creatinine, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and pro-inflammatory cytokines; TNF-α and IL-1 β. Liver and kidney tissue samples were obtained for the histological examination and the determination of malondialdehyde (MDA) and glutathione (GSH) levels as well as myeloperoxidase (MPO) and Na+ /K+-ATPase activities. PYC treatment decreased the APAP-induced elevations in serum pro-inflammatory cytokines and reduced the impairment of liver and kidney functions. Furthermore, the increase in tissue lipid peroxidation and myeloperoxidase activity and the decrease in the GSH levels and Na+ /K+-ATPase activity by the APAP overdose were reversed by the PYC treatment. Besides, histologic findings reinforce the protective effect of PYC in APAP-induced hepatorenal damage. PYC, which appears to have restored the GSH and depressed neutrophil infiltration and the associated release of proinflammatory cytokines, merits consideration as an anti-oxidant and anti-inflammatory agent in preventing APAP-induced hepatorenal damage. © 2021 by the authors.
Keywords: Acetaminophen; Cytokine; Glutathione; Lipid peroxidation; Pycnogenol